2022
DOI: 10.1111/hiv.13323
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of HIV infection in Warsaw: Estimating the scale of the problem and demographic trends

Abstract: Background: Late diagnosis of a significant number of people with HIV remains a problem. This study analysed 1711 patients from the Hospital for Infectious Diseases in Warsaw who were diagnosed with HIV infection in 2008-2010 and 2016-2018. Methods: Patients with late diagnosis and advanced disease were distinguished on the basis of the consensus definition. In statistical analysis, nonparametric tests were used to compare the groups: the χ 2 test for categorized data and the Mann-Whitney U test for the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In another study from Belgium, similar risk factors were reported, including older age, male sex, heterosexual risk group and sub‐Saharan origin [ 6 ]. Similar findings have been reported in studies from Denmark [ 8 ], Germany [ 10 ], Italy [ 11 , 14 ], Switzerland [ 13 ], France [ 25 ] and Poland [ 9 ], where age, transmission risk group and origin were reported, with minor differences across the different settings. The differences in our study were the identification of PWID as an indicator of non‐late presentation and that origin was not associated with LP.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In another study from Belgium, similar risk factors were reported, including older age, male sex, heterosexual risk group and sub‐Saharan origin [ 6 ]. Similar findings have been reported in studies from Denmark [ 8 ], Germany [ 10 ], Italy [ 11 , 14 ], Switzerland [ 13 ], France [ 25 ] and Poland [ 9 ], where age, transmission risk group and origin were reported, with minor differences across the different settings. The differences in our study were the identification of PWID as an indicator of non‐late presentation and that origin was not associated with LP.…”
Section: Discussionsupporting
confidence: 87%
“…LP was more common among heterosexuals, people who inject drugs (PWID) and older people in the region [ 1 ]. In previous studies, major risk factors for LP included heterosexual transmission, and injection drug use, immigration status and older age [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth stressing that these two studies included data from the majority of Polish HIV centres. In the last study of Puła et al [22], the authors estimated the scale of LP in the Hospital for Infectious Diseases in Warsaw (the biggest HIV care centre in Poland) In our study, 23 patients (92%) were LPs, 22 patients (88%) had advanced disease, 19 patients (76%) were in the AIDS stage, and two patients (8%) died. Our study group of new HIV cases constitutes only 1.24% of the total number of patients with HIV linked to care in 2020-2021, but represents 19% of total AIDS cases and 2% of total HIV-related deaths in this COVID-19 pandemic period.…”
Section: Discussionmentioning
confidence: 52%
“…It is worth stressing that these two studies included data from the majority of Polish HIV centres. In the last study of Puła et al [ 22 ], the authors estimated the scale of LP in the Hospital for Infectious Diseases in Warsaw (the biggest HIV care centre in Poland) during two periods of time: 2008–2010 and 2016–2018. In this study 42.7% and 44.7% of newly HIV diagnosed patients in 2008–2010 and 2016–2018, respectively, were LP.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in CD4 counts between the two measurements was statistically significant ( p = 0.001). In the years 2016–2018, no spontaneous increase in the CD4 count was found in any patient, which was probably related to the earlier initiation of treatment in this group [2].…”
Section: Resultsmentioning
confidence: 99%